Novel PSI domains in plant and animal H+-inositol symporters. - Dotzauer, Dorina; Wolfenstetter, Susanne; Eibert, Dorothee; Schneider, Sabine; Dietrich, Petra; Sauer, Norbert (Traffic (Copenhagen, Denmark), 2010)
Inositols are indispensable components of cellular signaling molecules, and impaired cytoplasmic inositol concentrations affect cellular development. Although most cells can synthesize inositol de novo, plasma membrane-localized inositol uptake systems are indispensable for normal development. Here, we present in-depth functional analyses of plasma membrane-localized H(+)-inositol symporters from human and from the higher plant Arabidopsis thaliana. Sequence comparisons, structural and phylogenetic analyses revealed that these transporters possess conserved extracellular loop domains that represent homologs of plexins/semaphorin/integrin (PSI) domains from animal type I receptors. In these receptors, PSI domains modulate intracellular signaling via extracellular protein-protein interactions. Comparisons of H(+)-inositol symporters with wild type, mutated and truncated PSI domains in different expression systems showed that removal of the entire loop domain increased the V(max) of inositol uptake. Finally, we show that the PSI domains are targets for Ni(++) ions that cause a complete loss of transport activity. A possible role of Ni(++)-binding to PSI domains in Ni(++)-induced carcinogenicity is discussed.